Targeting NAT10 Induces Apoptosis Associated With Enhancing Endoplasmic Reticulum Stress in Acute Myeloid Leukemia Cells - Zi, Jie; Han, Qi; Gu, Siyu; McGrath, Mary; Kane, Shriya; Song, Chunhua; Ge, Zheng (Frontiers in Oncology, 2020)
N-acetyltransferase 10 (NAT10) has oncogenic properties in many tumors through its role in different cellular biological processes. NAT10 is also a potential biomarker in acute myeloid leukemia (AML); however, the mechanisms underlying NAT10’s contribution to disease states and the effect of targeting NAT10 as a therapeutic target remain unclear. NAT10 was found to be highly expressed in patients with AML, and increased NAT10 expression was associated with poor outcomes. Additionally, targeting NAT10 via the shRNA knockdown as well as its pharmacotherapeutic inhibitor resulted in inhibition of cell proliferation, induction of cell cycle arrest in the G1 phase, and apoptosis in AML cells. Moreover, NAT10 induces cell cycle arrest by decreasing expression of CDK2, CDK4, CyclinD1, Cyclin E while simultaneously increasing the expression of p16 and p21. Targeting NAT10 induces ER stress through the increased expression of GRP78 and the cleavage of caspase 12, which are classical markers of ER stress. This triggered the Unfolded Protein Response (UPR) pathway by consequently increasing the expression of IRE1, CHOP, and PERK, all of which play crucial roles in the UPR pathway. Targeting NAT10 also activated the classical apoptotic pathway through the upregulation of the Bax/bak and the concurrent downregulation of Bcl-2. In summary, our data indicate that targeting NAT10 promotes ER stress, triggers the UPR pathway, and activates the Bax/Bcl-2 axis in AML cells. Our results thus indicate a novel mechanism underlying the induction of NAT10 inhibition-mediated apoptosis and reveal the potential for the therapeutic effect of a NAT10 specific inhibitor in AML.